2019
DOI: 10.1111/nbu.12371
|View full text |Cite
|
Sign up to set email alerts
|

Using social norms to encourage healthier eating

Abstract: What and how much people choose to eat is influenced by social context. People tend to use the eating habits of others as a guide to appropriate consumption. This suggests that one way of encouraging healthier eating would be to provide information about the healthy eating choices of others. Research conducted as part of an Economic and Social Research Council‐funded project investigated the effect of providing information about how others eat on the purchase and consumption of vegetables in both laboratory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 66 publications
(137 reference statements)
1
34
0
Order By: Relevance
“…Most experimental research on social norms and eating behavior seem in favor of using descriptive norms to influence eating behavior because they are found to have greater effect on eating behavior compared to injunctive norms, and may avoid potential reactance effects (48-50). Although we did not manipulate the perceived norms in our study, our findings are important for this field of research when aiming to develop interventions with long term impact (11,20,51). In our study, we did not find an effect over time of perceived peer and parental descriptive norms on (un)healthy snack intake.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Most experimental research on social norms and eating behavior seem in favor of using descriptive norms to influence eating behavior because they are found to have greater effect on eating behavior compared to injunctive norms, and may avoid potential reactance effects (48-50). Although we did not manipulate the perceived norms in our study, our findings are important for this field of research when aiming to develop interventions with long term impact (11,20,51). In our study, we did not find an effect over time of perceived peer and parental descriptive norms on (un)healthy snack intake.…”
Section: Discussionmentioning
confidence: 49%
“…Research has shown that their (snack) food intake is strongly influenced by close social connections (10), which provides opportunities for prevention. The development of effective strategies to improve adolescents' eating behaviors requires an understanding of how significant others (i.e., parents and peers) influence eating behavior (11). In addition, it is important to examine whether adolescents' own eating behavior influences their perception of what close others do and approve of.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most experimental research on social norms and eating behavior seem in favor of using descriptive norms to influence eating behavior because they are found to have greater effect on eating behavior compared to injunctive norms, and may avoid potential reactance effects (48)(49)(50). Although we did not manipulate the perceived norms in our study, our findings are important for this field of research when aiming to develop interventions with long term impact (11,20,51). In our study, we did not find an effect over time of perceived peer and parental descriptive norms on (un)healthy snack intake.…”
Section: Discussionmentioning
confidence: 89%
“…These social norms have been identified as powerful mechanisms in determining adolescents' and adults' consumption behavior (12,(14)(15)(16)(17)(18)(19). Although the research field on social norms in adolescents is still evolving, few experimental normative studies have already shown promising findings to promote healthy consumption behavior (11). For example, an intervention study successfully targeted water drinking among schoolchildren by influencing the peer group norm (20).…”
Section: Introductionmentioning
confidence: 99%